Perancangan Sistem Informasi Pengolahan Data Rekam Medis Elektronik Guna Menunjang Tata Kelola Pelaporan Rawat Jalan - Hermawan, Putra Pangestu; Abdussalaam, Falaah; Sari, Irda (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Recording and reporting medical records is the main activity in health service institutions, and hospital information systems play an essential role in this process. Outpatient data processing at XYZ Hospital uses spreadsheets and Google Sheets even though it has yet to implement SIMRS fully. Because the data in the SIMRS must be changed for each spreadsheet report, there are several reporting problems. Therefore, the authors begin to develop a web-based outpatient reporting system after researching the need for more efficient applications. This study uses a qualitative approach to data collection through interviews and observations, focusing on developing a waterfall software. The results showed that searching and managing patient data and making outpatient recapitulation reports became easier for medical record officers. Implementing this system brings several concrete impacts, including reducing human errors in data recording, increasing the speed of access to medical information, and increasing time efficiency in making reports. This system also allows better data integration between hospital departments, improving patient care coordination and the overall quality of health services.